The attractiveness of a food based lure and its component volatiles to the stored-grain pest Oryzaephilus surinamensis (L.). (September 2022) - Sabier, Maidinai; Wang, Jirui; Zhang, Tao; Jin, Jiande; Wang, Zhunjing; Shen, Bo; Deng, Jianyu; Liu, Xingquan; Zhou, Guoxin
Abstract: The sawtoothed grain beetle Oryzaephilus surinamensis L . is a major worldwide pest of stored products. In this study, an effective lure for O. surinamensis was developed by blending six foods with high attractiveness, which consisted of oatmeal, fig, sucrose, hawthorn, cashew, millet, and wolfberry. Its luring ability varied at different population densities of insects and different environmental temperatures. Moreover, the food-based lure could elicit other stored-grain pests red flour beetle Tribolium castaneum (Herbst), rusty grain beetle Cryptolestes ferrugineus (Stephens), corn weevils Sitophilus zeamais (Motschulsky) and lesser grain borer Rhyzopertha dominica (Fabricius). Furthermore, six compounds including nonanal, β -caryophyllene, dodecane, tridecane, dibutyl phthalate, methyl palmitate were identified from the lure volatiles which could significantly attract O . surinamensis by GC-EAD and GC-MS technology. Although three chemicals, nonanal, dodecane, and β-caryophyllene, were discovered to have both electrophysiological and behavioral bioactivity to O. surinamensis, only the chemical mixture containing all six compounds demonstrated effective attractiveness as well as the food-based lure. Our results indicated that food volatiles play an essential role in attracting stored-product pests and the food- and bioactive chemicals-based lures are both effective as attractants to O. surinamensis, which may be used in monitoring and controlling stored grain insect. Highlights: Food mixtures and its volatiles had attraction activity to four kinds of stored grain pests. Food mixture can successfully trap stored grain pests in granary. Food volatile could elicited the EAG responses of O. surinamensis . Three chemicals identified from food volatiles nonanal, dodecane, and ß -caryophyllene also can attract O. surinamensis .